Is Product Placement Really Worse Than Traditional Commercials? Cognitive Load and Recalling of Advertised Brands - Grzyb, Tomasz; Dolinski, Dariusz; Kozłowska, Agnieszka (Frontiers in Psychology, 2018)
Considering the large number of adverts inundating the average consumer every day, the marketing industry is seeking methods to reach clients in a more subtle manner than traditional marketing messages. One such tool is product placement. The article addresses issues of effectiveness of product placement in comparison to a traditional commercial. The objective of the study was to check how participants would recall the content of persuasive messages in conditions of artificially-inducted cognitive load (in conditions of traditional advertisement and product placement). Two studies were conducted – a pilot study intended to assess the usefulness of the selected stimuli, and the main experiment. The experiment devoted to this question was planned using an ANOVA scheme 2 (Type of advert: traditional vs. product placement) x 2 (neutral conditions vs. cognitive load). It turned out that the commercial was better retained in neutral conditions than in conditions of cognitive load. The traditional commercial was remembered better than product placement. From the perspective of the study’s ecological validity, of importance is also comparison of retention of brands viewed in a traditional commercial in conditions of cognitive load with retention of brands in conditions of product placement without load. These comparisons indicate the superiority of product placement – brands presented in this manner were more frequently recalled by viewers.